2019
DOI: 10.1088/1361-6560/ab1e9d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intravenous contrast agent on dose calculation in proton therapy using dual energy CT

Abstract: The purpose of this study is to evaluate the effect of an intravenous (IV) contrast agent on proton therapy dose calculation using dual-energy computed tomography (DECT). Two DECT methods are considered. The first one, , attempts to accurately predict the proton stopping powers relative to water (SPR) of contrast enhanced (CE) DECT images, while the second generates a virtual non-contrast (VNC) volume that can be processed as a native non-contrast (NC) one. Both methods are compared against single-energy compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Thus, the reported advantages on RSP maps of other DECT scanners are not achievable on the Twinbeam. This finding is consistent with other authors who found inferior performance of the Twinbeam system for virtual monoenergetic and virtual non‐contrast imaging 50,51 . Using images with reduced stopping power uncertainty could allow for reduced margins when designing treatment plans, possibly opening pathways to dose escalation and increased organ‐at‐risk sparing 52 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the reported advantages on RSP maps of other DECT scanners are not achievable on the Twinbeam. This finding is consistent with other authors who found inferior performance of the Twinbeam system for virtual monoenergetic and virtual non‐contrast imaging 50,51 . Using images with reduced stopping power uncertainty could allow for reduced margins when designing treatment plans, possibly opening pathways to dose escalation and increased organ‐at‐risk sparing 52 .…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with other authors who found inferior performance of the Twinbeam system for virtual monoenergetic and virtual noncontrast imaging. 50,51 Using images with reduced stopping power uncertainty could allow for reduced margins when designing treatment plans, possibly opening pathways to dose escalation and increased organ-at-risk sparing. 52 If dose could be calculated on daily CBCT using the proposed method, the margins typically added for setup uncertainties could be reduced since the patient would not be moved between "simulation" and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the DL method can provide benefits for particle therapy, where dose calculations using CT number‐to‐stopping power conversion could be more sensitive to uncertainties in the CT numbers. According to a recent study that compared VNC DECT and CE images for proton therapy, the error in the stopping power ratio due to the range error was reduced to <1 mm in the VNC DECT images, whereas it was 3.2 mm in the CE images . However, our findings suggest that non‐negligible errors can occur in VNC DECT ‐based dose calculations when the beam passes through a bone structure.…”
Section: Discussionmentioning
confidence: 49%
“…According to a recent study that compared VNC DECT and CE images for proton therapy, the error in the stopping power ratio due to the range error was reduced to <1 mm in the VNC DECT images, whereas it was 3.2 mm in the CE images. 37 However, our findings suggest that nonnegligible errors can occur in VNC DECT -based dose calculations when the beam passes through a bone structure. Although the proposed DL method provided promising results in treatment planning, the VNC DL images should be used for dose calculation, not for other tasks.…”
Section: Discussionmentioning
confidence: 66%
“…Such VNC approach requires the attenuation coe cients of contrast enhanced agents of two DECT spectra. It has disadvantages of high complication coe cient, high requirements on machine performance, and high cost [11] . VNC approach is widely applied in diagnostic imaging [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%